2022
DOI: 10.1002/solr.202200691
|View full text |Cite
|
Sign up to set email alerts
|

An Alcohol‐Soluble N‐Annulated Perylene Diimide Cathode Interlayer for Air‐Processed, Slot‐Die Coated Organic Photovoltaic Devices and Large‐Area Modules

Abstract: Cathode interlayers (CILs) in organic photovoltaics (OPVs) are actively being researched as they are critical for device stability and performance. Herein, N‐annulated perylene diimide with a 2‐ethyl‐hexyl side chain (PDIN‐EH) is demonstrated, which is facile to synthesize as compared with conventional CILs such as PFN‐Br, exhibits solubility, and subsequent processability from ethanol. The PDIN‐EH is evaluated as a CIL in an air‐processed, slot‐die coated OPV consisting of PEDOT:PSS as the hole transport laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…OPVs are considered a leading alternative energy source candidate, whereby abundant solar energy that irradiates the bulk heterojunction (BHJ) photoactive layer facilitates photon harvesting and exciton splitting to generate electricity. ,, The development of advanced π-conjugated materials has swiftly overtaken conventional fullerenes because the synthetic versatility of π-conjugated materials allows for better optical and energetic matching with electron donor polymer(s) in the photoactive layer. , In fact, recent reports have even shown that pairing highly fused A–D–A systems (i.e., Y6) with appropriate donor polymer materials (i.e., PM6) can lead to power conversion efficiencies (PCEs) exceeding 18%. However, limitations in the PM6:Y6-based OPV device size and air stability have prompted our group (and many others) to fabricate large-scale, roll-to-roll solution-processable OPV devices. Although the use of ambient conditions lowered the overall PCE of these PM6:Y6-based devices, we have found the integration of NPDI-derived materials as the CIL can significantly improve the overall OPV device PCE and stability. …”
Section: Organic Photovoltaic Device Datamentioning
confidence: 89%
See 2 more Smart Citations
“…OPVs are considered a leading alternative energy source candidate, whereby abundant solar energy that irradiates the bulk heterojunction (BHJ) photoactive layer facilitates photon harvesting and exciton splitting to generate electricity. ,, The development of advanced π-conjugated materials has swiftly overtaken conventional fullerenes because the synthetic versatility of π-conjugated materials allows for better optical and energetic matching with electron donor polymer(s) in the photoactive layer. , In fact, recent reports have even shown that pairing highly fused A–D–A systems (i.e., Y6) with appropriate donor polymer materials (i.e., PM6) can lead to power conversion efficiencies (PCEs) exceeding 18%. However, limitations in the PM6:Y6-based OPV device size and air stability have prompted our group (and many others) to fabricate large-scale, roll-to-roll solution-processable OPV devices. Although the use of ambient conditions lowered the overall PCE of these PM6:Y6-based devices, we have found the integration of NPDI-derived materials as the CIL can significantly improve the overall OPV device PCE and stability. …”
Section: Organic Photovoltaic Device Datamentioning
confidence: 89%
“…In this preliminary CIL thickness-dependence experiment, it was observed that CIL thin films <10 nm gave the best OPV device performance and that OPV device PCE significantly dropped if the CIL thin film thickness exceeded 15 nm. These results suggest that while molecule A can effectively modify the energy levels of the PM6:Y6/Ag interface in such a way that charge carrier mobility is improved, molecule A can also act as a barrier to charge transport and collection if the CIL thin film is too thick. , Since we expect similar thickness-dependence behavior for CIL molecules B–D , all OPV devices were processed using 0.5 mg mL –1 solutions of A–D in EtOAC.…”
Section: Organic Photovoltaic Device Datamentioning
confidence: 97%
See 1 more Smart Citation
“…It is worth noting that in order to prepare PDI derivatives with certain solubility in alcohols, to meet the processing needs of interface layers in OSCs, the skeleton of PDI usually needs to be modified with amino, amino-N-oxide, or aliphatic amine groups. [39][40][41] In this case, the PDI-based carbolong complexes 1a-1c and 2a-2b are soluble in alcohols, and they were chosen as the ETL materials in OSCs to evaluate their photovoltaic performances. The devices are fabricated with the architecture of ITO/PEDOT:PSS/ PM6:Y6/ETL (1 mg mL −1 )/Ag (see Supporting Information for details).…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…With the constant development of photoactive materials and device engineering, in recent years, bulk heterojunction (BHJ) organic solar cells (OSCs) have made significant achievements. [1][2][3][4][5][6][7][8][9][10][11][12] Power conversion efficiencies (PCEs) of over 19% have been achieved for both single junction and tandem OSCs. [13][14][15][16][17][18][19][20][21][22] Combining the unique advantages of light weight, large-area fabrication, and flexibility, BHJ-OSCs show great commercialization prospects.…”
Section: Introductionmentioning
confidence: 99%